2019
DOI: 10.1002/eng2.12024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of thermal performance of single‐walled carbon nanotube nanofluid under turbulent flow conditions

Abstract: In this paper, a numerical study is performed to investigate the effect of Reynolds number and nanoparticle concentration on the thermal performance of single‐walled carbon nanotubes (SWCNTs) nanofluids flowing through a straight pipe with constant heat flux in a turbulent flow regime. The governing equations (continuity, momentum, energy, rate of turbulent production, and rate of turbulent dissipation) are solved using a computational fluid dynamic approach (ie, finite volume method). In the sensitivity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…These hybrid heat transfer fluids have been found to possess high thermal conductivity compared with the base fluid and also have some advantages over conventional heat transfer fluids, which include higher heat conduction rate, lower pumping power, stability, and among others. 3,4 Various works on the enhancement of CHTP using geometry modification such as the usage of ribs, 5,6 vortex generator, [7][8][9] wavy channel, 10,11 twisted tape inserts, [12][13][14] corrugated tube, [15][16][17] noncircular cross-section, [18][19][20] helical tube, 21 and converging pipe 22 have been reported in the literature. In addition, among the various geometry modifications examined so far, the inwardly corrugated pipe is preferable due to its high thermal efficiency and ease of maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hybrid heat transfer fluids have been found to possess high thermal conductivity compared with the base fluid and also have some advantages over conventional heat transfer fluids, which include higher heat conduction rate, lower pumping power, stability, and among others. 3,4 Various works on the enhancement of CHTP using geometry modification such as the usage of ribs, 5,6 vortex generator, [7][8][9] wavy channel, 10,11 twisted tape inserts, [12][13][14] corrugated tube, [15][16][17] noncircular cross-section, [18][19][20] helical tube, 21 and converging pipe 22 have been reported in the literature. In addition, among the various geometry modifications examined so far, the inwardly corrugated pipe is preferable due to its high thermal efficiency and ease of maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids are a class of improved heat transfer fluids obtained by dispersing small amounts of nanoparticles of higher thermal conductivity (SiO 2 , Al 2 O 3 , TiO 2 , and Fe 2 O 3 ) in base fluid (water and ethylene glycol). These hybrid heat transfer fluids have been found to possess high thermal conductivity compared with the base fluid and also have some advantages over conventional heat transfer fluids, which include higher heat conduction rate, lower pumping power, stability, and among others 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…A literature survey showed that among various pipe modifications examined so far, the converging pipe is among the preferable ones because of its improved heat transfer performance (HTP), which is accompanied by a relatively moderate pressure drop (dP). [1][2][3][4][5][6] Nonetheless, we noticed that less attention is being given to the study of HTP and entropy production rates (EPR) of nanofluids in converging pipes, especially in turbulent flow regimes. Among the few works available includes those of Iweka and Fadodun 7 who investigated the laminar HTP of Al 2 O 3 /H 2 O nanofluid in a Bessel-like converging pipe (BCP) using the finite volume method (FVM).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, passive methods of enhancing convective heat transfer such as geometric modification (usage of converging pipe, wavy channel, helical coil‐insert, grooved channel, and corrugated pipe in place of straight pipe [SP]) and usage of nanofluid as a heat transfer fluid are attracting lots of attention from researchers because they hold the key to improving thermal performance and engendering miniaturization. A literature survey showed that among various pipe modifications examined so far, the converging pipe is among the preferable ones because of its improved heat transfer performance (HTP), which is accompanied by a relatively moderate pressure drop (dP). 1–6 Nonetheless, we noticed that less attention is being given to the study of HTP and entropy production rates (EPR) of nanofluids in converging pipes, especially in turbulent flow regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the influences of velocity slip on MHD flow of Eyring‐Powel nanofluid past isothermal sphere were deliberated by Swarnalathamma . The thermal performance of single‐walled carbon nanotube nanofluid under turbulent flow conditions was investigated by Fadodun et al Their results indicates that convective heat transfer (average Nusselt number) increases by 7.48% while the pressure drop and pumping power increase by 119% and 199%, respectively. Mathematical modeling of non‐Newtonian fluid with chemical aspects via numerical technique was investigated by Hayat et al IjazKhan et al examined new thermodynamics of entropy generation minimization in the presence of nonlinear thermal radiation and nanomaterial.…”
Section: Introductionmentioning
confidence: 99%